2013
DOI: 10.3109/08880018.2013.831961
|View full text |Cite
|
Sign up to set email alerts
|

Avascular Necrosis of Femoral Head as the Initial Manifestation of CML

Abstract: A 12-year-old female is reported who presented with right hip pain for 6 months. With massive splenohepatomegaly and leukocytosis, CML was suspected and confirmed on bone-marrow examination and cytogenetics. Further investigations confirmed avascular necrosis (AVN) of the right femoral head. CML was treated by hydroxyurea, followed by imatinib. AVN was managed conservatively; patient demonstrated progressive improvement, though a mild limp in the gait was persisting at 22 months. AVN as the initial manifestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Rottenstreich et al reported a case of bilateral calf pain and retinal hemorrhages due to leukostasis in a young CML male [22] and Awh et al reported a case with leukostasis related retinopathy in a 41-year-old man with CML and severe hyperleukocytosis successfully treated with dasatinib [23]. Three different groups [6,24,25] presented three cases of femoral necrosis as initial presentation of CML with hyperleukocytosis. Tsai et al reported a sudden hearing loss as the initial manifestation of CML in a child [26], while Woldag et al reported a labyrinth apoplexy in a 45-year-old patient with CML and hyperleukocytosis [27] and Frankel et al reported a case of "acral lividosis" in a similar patient [28].…”
Section: Discussionmentioning
confidence: 99%
“…Rottenstreich et al reported a case of bilateral calf pain and retinal hemorrhages due to leukostasis in a young CML male [22] and Awh et al reported a case with leukostasis related retinopathy in a 41-year-old man with CML and severe hyperleukocytosis successfully treated with dasatinib [23]. Three different groups [6,24,25] presented three cases of femoral necrosis as initial presentation of CML with hyperleukocytosis. Tsai et al reported a sudden hearing loss as the initial manifestation of CML in a child [26], while Woldag et al reported a labyrinth apoplexy in a 45-year-old patient with CML and hyperleukocytosis [27] and Frankel et al reported a case of "acral lividosis" in a similar patient [28].…”
Section: Discussionmentioning
confidence: 99%
“…Leukostasis, thrombocytosis, and bone marrow hypercellular infiltration have been proposed to induce early ON development. In combination with changes in bone homeostasis during puberty, these changes caused by leukemia could create a state of ischemia in the bone that could induce ON.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier progression to puberty in females compared with males alters hormone levels, growth plate maturation, and lipid metabolisms. 5 Leukostasis, thrombocytosis, 16 and bone marrow hypercellular infiltration 10,17 have been proposed to induce early ON development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations